2017
DOI: 10.3390/ijms19010021
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomics Analysis on Excellent Meat Quality Traits of Skeletal Muscles of the Chinese Indigenous Min Pig Compared with the Large White Breed

Abstract: The Min pig (Sus scrofa) is a well-known indigenous breed in China. One of its main advantages over European breeds is its high meat quality. Additionally, different cuts of pig also show some different traits of meat quality. To explore the underlying mechanism responsible for the differences of meat quality between different breeds or cuts, the longissimus dorsi muscle (LM) and the biceps femoris muscle (BF) from Min and Large White pigs were investigated using transcriptome analysis. The gene expression pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
36
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(44 citation statements)
references
References 35 publications
1
36
3
Order By: Relevance
“…The Min pig (such as Heilongjiang Province), a well-known Chinese fat-type breed, is famous for its high IMF, superior meat quality, and stress resistance. Compared with Min pig, the Large White pig has a faster growth rate and higher lean meat ratio (Liu et al 2017).…”
Section: Discussionmentioning
confidence: 99%
“…The Min pig (such as Heilongjiang Province), a well-known Chinese fat-type breed, is famous for its high IMF, superior meat quality, and stress resistance. Compared with Min pig, the Large White pig has a faster growth rate and higher lean meat ratio (Liu et al 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Pigs are an important source of meat production worldwide [1,2]. With improvements in individual living standards, pork plays an increasing number of important roles in citizens' lives, especially in Chinese food [3].…”
Section: Introductionmentioning
confidence: 99%
“…Similar results of meat sensory quality were also found in the Anqingliubai and the Yorkshire pigs, which suggested that the Anqiuliubai pigs had greater meat sensory quality than that in the Yorkshire pigs. Furthermore, the Jinhua pig (Guo et al 2011;Miao et al 2009), Meishan pig (Suzuki et al 1991), Taihu pig (Li et al 2008), and Min pig (Liu et al 2017) showed better meat sensory quality compared with the Landrace pig, Duroc × Landrace pig, Landrace pig, and Yorkshire pig, respectively. It has been demonstrated that lipid oxidation affected the sensory quality in the post-slaughter meat of pig (Chen et al 2018).…”
Section: Discussionmentioning
confidence: 94%
“…Pig breed is one of the main factors affecting pork sensory quality (Pugliese and Sirtori 2012;Kouba and Sellier 2011;Zheng et al 2018). Generally, the obese-pig and lean-pig breeds showed different meat sensory quality (Guo et al 2011;Miao et al 2009;Liu et al 2017). Shen et al (2014) reported Chinese Tibetan pig and Liang-Shan pig have higher IMF, pH 45min , pH 24h , pH 48h and pH 72h , but lower DL 24h and DL 48h than DLY pig, and there was a significant effect of breed among three breeds.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation